Commodity dependence and price volatility in least developed countries: A structuralist computable general equilibrium model with applications to Burkina Faso, Ethiopia and Mozambique - Rudi von Arnim; Bernhard Tröster; Cornelia Staritz; Werner Raza (Austrian Foundation for Development Research (ÖFSE), 2015)
Many least developed countries (LDCs) face commodity dependence on the export and import side. This paper develops a structuralist computable general equilibrium model for commodity-dependent LDCs and simulates global commodity price shocks for Burkina Faso, Ethiopia and Mozambique. Results show important macroeconomic and distributional effects. Although increasing export commodity prices are beneficial, the high correlation with import commodity prices causes low or even negative combined effects. The magnitude of effects depends on the economic structure, the degree of import and export dependence, the production structure of the key commodity sectors and the distribution of windfall profits.
Keywords: 330; Commodity Dependence; Price Volatility; Sub-Saharan Africa